Implementation of the 7 Habits of Great Indonesian Children Program to Realize a Character-Based School Culture at SMPN 3 Baleendah - Waska Warta; Ana Suryana; Mulyati; Rina Nuraeni (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2026)
This study aims to analyze the effectiveness of school management in implementing the